Análise da Contribuição do Uso do Gerador Síncrono virtual Como Técnica de Controle em Sistemas elétricos de Potência - Broedel, Dayane Corneau (2017)
Electric power systems have to convey electricity at synchronized frequency and voltagein order to be reliable. Voltage control systems can use different strategies to achievevoltage regulation - reactive power compensation being one of them. On the other hand,frequency control is traditionally obtained by regulation of large scale synchronous machinesoperations. However, the increasing use of alternative energy sources and the operation ofthese generators in parallel with the traditional power systems emphasize the importanceof studying the integration of these generation units. An aspect to be analyzed is theimpact in the reduction of the system total inertia, that might increase frequency andvoltage variations, affecting the power system stability when facing different types ofdisturbance. In this context, this work is dedicated to discuss the use of the concept ofadditional virtual inertia, where each generation unit behaves as a virtual synchronousgenerator, in comparison with the traditional PQ technique for power control of interfaceinverters. Simulation results show the virtual generator contribution to the stability of aknown system, the IEEE-14 Bus.